The integration of structured physical training and nutrition to enhance seafarer endurance and career preparedness in maritime education - Riyanto Riyanto; Tri Cahyadi; Winarno Winarno; Irfan Faozun; Larsen Barasa; Diah Zakiah; Natanael Suranta; Marudut Bernadtua Simanjuntak (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Maritime professionals face intense physical and mental demands, yet vocational education often overlooks structured fitness and balanced nutrition, focusing primarily on technical skills. This study explored the impact of integrating these elements on cadet endurance, cognitive function, and career sustainability, addressing a gap in existing research that rarely assesses fitness and nutrition systematically. Through qualitative insights from lecturers, graduates, and cadets, this research aimed to identify implementation challenges and evaluate perspectives on fitness scheduling, dietary adequacy, and career preparedness, ultimately offering practical recommendations for enhancing maritime training programs. Methods: This study employed a qualitative descriptive approach, utilizing semi-structured interviews, focus group discussions, and participant observation to explore the integration of physical training and nutrition in maritime education. Participants included 5 lecturers, 10 graduates, and 25 cadets, providing diverse perspectives. Data analysis followed a thematic qualitative approach, including cross-group comparisons and narrative synthesis, to identify recurring patterns and develop evidence-based recommendations for enhancing maritime training programs. The study assessed cadet performance, endurance, and career preparedness through indicators such as engagement in physical activities and perceived nutritional adequacy. The findings aimed to contribute to a more resilient and health-conscious maritime workforce. Results: Findings indicate that structured physical training improves cadet endurance and teamwork, while nutritional planning remains inconsistent, affecting energy levels and long-term health. Cadets expressed challenges in balancing fitness with coursework, suggesting the need for optimized scheduling and nutritional education. Conclusions: To enhance maritime workforce sustainability, institutions should integrate structured physical training, standardized meal plans, and nutritional awareness programs. Future research should assess long-term effects of fitness and dietary habits on seafarer health and career performance.